Zur Biologie des Biberkäfers Platypsyllus castoris Ritsema (Coleoptera). - Piechocki, Rudolf (Contributions to Entomology = Beiträge zur Entomologie, 1959)
There are made up reports on Platypsyllus castoris Rits. on Castor fiber albicus Matschie with observations on nutrition, development and pupation of the larvae. The morphology of the last larval instar is illustrated by 2 figures.